Induction of a Lactogenic Receptor in Rat Liver: Influence of Estrogen and the Pituitary - Posner, Barry I. (1974)
A receptor exists in female rat liver with high specificity for lactogenic hormones. Previous work showed the receptor level increased at the time of puberty in female but not male animals. Pregnancy caused a further substantial increase. Here we show that estrone (50 μg/day) administration to male rats induced a 10- to 30-fold increase in specific binding of ovine prolactin and human growth hormone after 8-12 days with a significant increase first seen after 4 but not 2 days of injection. In females, this regimen increased binding to pregnancy levels. In prepuberal (20-days-old) male and female rats, estrone was also markedly stimulatory. The binding sites for ovine prolactin and human growth hormone were of high affinity in liver membranes from both female and estrone-treated male rats (K(a) = 0.6 to 1.4 × 10(9) M(-1)). Estrone and estradiol were equally effective in inducing the lactogenic receptor. Estriol (50 μg/day), progesterone (500 μg/day), human placental lactogen (1 mg/day), and testosterone (100 μg/day) were without influence. Hypophysectomy drastically decreased the levels of lactogenic receptor in mature female rats, and estrogen treatment failed to restore receptor levels to normal. Hypophysectomized male rats were also unresponsive to estrogen. Throughout these studies the specific binding of (125)I-labeled insulin remained relatively constant. This work demonstrates estrogen induction of a lactogenic receptor. The pituitary gland appears to have a critical, though presently undefined, role in the induction process.